Konsep Pendidikan Islam Humanis dalam Perspektif KH. Abdurrahman Wahid - Alief Irfan Choiri; Saeful Anam (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This research aims to explore and analyze the thoughts of KH. Abdurrahman Wahid (Gus Dur) on Islamic education grounded in humanistic values, emphasizing the importance of an educational approach that transcends mere cognitive-intellectual dimensions by upholding human dignity, freedom of thought, and respect for plurality. The study employs a qualitative approach with a library research method. Data were collected through documentation studies, particularly from Gus Dur’s seminal works such as Islamku, Islam Anda, Islam Kita and Ilusi Negara Islam, as well as other relevant secondary sources. The data were analyzed using content analysis techniques.The findings show that Gus Dur's concept of humanist Islamic education emphasizes inclusivity, tolerance, and freedom of thought, while firmly grounded in the principles of equality, justice, liberation, and respect for diversity. These values form a strong philosophical and ethical foundation for Islamic education in a pluralistic and democratic Indonesian context. This study contributes to the academic discourse by offering a comprehensive reconstruction of Gus Dur’s educational thought, which remains underexplored in the context of contemporary Islamic education.